2015
DOI: 10.1017/s0950268815002782
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and relatedness of Shiga toxin-producingEscherichia coliandCampylobacter jejunibetween farms in a dairy catchment

Abstract: The aim of this study was to examine the population structure, transmission and spatial relationship between genotypes of Shiga toxin-producing Escherichia coli (STEC) and Campylobacter jejuni, on 20 dairy farms in a defined catchment. Pooled faecal samples (n = 72) obtained from 288 calves were analysed by real-time polymerase chain reaction (rtPCR) for E. coli serotypes O26, O103, O111, O145 and O157. The number of samples positive for E. coli O26 (30/72) was high compared to E. coli O103 (7/72), O145 (3/72)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…O145 was detected in 3% of FDE and 9% of calf faeces by culture-based methods, whereas no isolates from the O111 or O157 serogroups were obtained. The molecular prevalences in our study are in general greater than those reported in New Zealand (Irshad et al 2016;Jaros et al 2016). It is possible that the greater prevalences observed in our study resulted from analysing faecal material that was naturally shed by several animals, which may have attenuated the animal effect.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…O145 was detected in 3% of FDE and 9% of calf faeces by culture-based methods, whereas no isolates from the O111 or O157 serogroups were obtained. The molecular prevalences in our study are in general greater than those reported in New Zealand (Irshad et al 2016;Jaros et al 2016). It is possible that the greater prevalences observed in our study resulted from analysing faecal material that was naturally shed by several animals, which may have attenuated the animal effect.…”
Section: Resultscontrasting
confidence: 67%
“…The molecular prevalences in our study are in general greater than those reported in New Zealand (Irshad et al . ; Jaros et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Isolates from this study were obtained from RAMS re-enrichments (buffered peptone water, 37°C, 24 h) whereafter thawing at room temperature for 5 min, 100 µl of each sample was re-enriched in 10 ml of buffered peptone water at 37°C for 6 h. Template DNA for PCR was prepared from a 1 ml aliquot of re-enriched broth using 2% Chelex (Bio-Rad, Auckland, New Zealand) solution as described previously [19]. Real-time PCR (RT–PCR) was performed to detect the presence of serogroup-specific loci wzx (O26) [20], wzx (O103) [21], wbdI (O111) [20] and wzx1 (O145) genes [22] using previously described methods [23].…”
Section: Methodsmentioning
confidence: 99%
“…Enrichments that provided O26, O103, O111 or O145 RT–PCR-positive samples were subjected to immuno-magnetic separation (IMS) using serotype-specific beads in an attempt to isolate each respective serogroup [23]. The IMS bead suspension (100 µl) was inoculated onto rhamnose MacConkey agar supplemented with cefixime (50 µg/ml) and potassium tellurite (2·5 mg/ml) (CT-RMAC) (Fort Richard, Auckland, New Zealand) for isolation of O26 and sorbitol MacConkey agar (SMAC) (Fort Richard, Auckland, New Zealand) for isolation of O103, O111 and O145.…”
Section: Methodsmentioning
confidence: 99%
“…Research is limited on the prevalence and distribution of AMR and zoonotic bacteria in New Zealand waterways because growing, isolating, and identifying all potential target organisms from the potential millions contained in a single sample is time consuming and costly. In part, this is because identification through culturing is complicated by diverse metabolic requirements and identifying individual organisms present in a sample would require multiple culture methods ( Jaros et al, 2013 ; Irshad et al, 2016 ). In studies of ESBLs and STEC strains from ruminant faeces and environmental samples the microbial communities are generally enriched prior to DNA-based testing ( Muirhead et al, 2004 ; Gluckman, 2017 ).…”
Section: Discussionmentioning
confidence: 99%